Case Report: Immunotherapy-induced myocarditis requiring pacemaker insertion in an older adult. what happens if we rechallenge? - Assaad, Wassim; El Meski, Nour; Fakhreddine, Omar; El Halabi, Tarek; Refaat, Marwan; Kreidieh, Firas (Frontiers in Oncology, 2026)
Immune checkpoint inhibitors (ICIs) have revolutionized the practice of oncology, becoming a cornerstone treatment for many cancers. Nivolumab, an antibody-targeting programmed cell death protein-1 (PD-1), and ipilimumab, an antibody-targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), are two ICIs that, when combined, lead to improved treatment responses and enhanced survival rates. However, dual immunotherapy can come at the expense of increased incidence of autoimmune-related adverse events. The mortality rate of ICI-induced myocarditis can be high, and therapy rechallenge can pose a significant risk of recurrence and severe complications. There is no consensus regarding therapy rechallenge after myocarditis, and this decision should be made in a multidisciplinary discussion following a patient-centered approach. In our paper, we report the case of an adult patient with metastatic renal cell carcinoma who developed multiorgan toxicity, including severe myocarditis that required pacemaker implantation, after a single cycle of ipilimumab and nivolumab. Importantly, we also report the consequences on her cardiac and safety profile following ICI rechallenge.